2000
DOI: 10.1046/j.1471-4159.2000.0750624.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Microtubule‐Associated Protein Tau Is a Substrate for Caspase‐3 and an Effector of Apoptosis

Abstract: Abstract:We have identified a class of tau fragments inducing apoptosis in different cellular contexts, including a human teratocarcinoma-derived cell line (NT2 cells) representing committed human neuronal precursors. We have found a transition point inside the tau molecule beyond which the fragments lose their ability to induce apoptosis. This transition point is located around one of the putative caspase-3 cleavage sites. This is the only site that can be effectively used by caspase-3 in vitro, releasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(91 citation statements)
references
References 47 publications
3
86
2
Order By: Relevance
“…In fact, the overexpression of tau (1-230) as well as full-length tau actually protected CGNs from apoptotic death ( Figure 5-7). This finding is apparently in contrast with previous reports regarding the proapoptotic effect of the prolin-rich region within the N-terminal tau domain, 16 but the different types of cellular models and experimental manipulations may be the basis of such discrepancy. Thus, the proapoptotic action was observed in cyclic non-neuronal cells, while the antiapoptotic effect that we found was in primary cultures of postmitotic neurons.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In fact, the overexpression of tau (1-230) as well as full-length tau actually protected CGNs from apoptotic death ( Figure 5-7). This finding is apparently in contrast with previous reports regarding the proapoptotic effect of the prolin-rich region within the N-terminal tau domain, 16 but the different types of cellular models and experimental manipulations may be the basis of such discrepancy. Thus, the proapoptotic action was observed in cyclic non-neuronal cells, while the antiapoptotic effect that we found was in primary cultures of postmitotic neurons.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the incomplete overlapping of the plasmids used to test the effect of tau on survival may add variances in the interpretation of the different results. In fact, the proapoptotic effect reported by Fasulo et al 16 was observed with a region of tau containing P1-P2 and R1, and lacking all the first 151 amino acids (tau (151-274)). In contrast, in our tau (1-230) construct R1 was absent and P2 was deleted from the last 12 aminoacids in which, for example, a functional SH3-binding domain is present.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Because of these differences, it is argued that human Tau, but not murine Tau, can exert neurotoxic effects. However, this hypothesis is contrasted by data showing that endogenous mouse Tau is required for Aβ-induced postsynaptic dysfunction and behavioral defects, [17][18][19][20][21][22][23][24] which suggest that murine Tau can carry out pathogenic functions that resemble that of human Tau AD.…”
Section: Introductionmentioning
confidence: 95%
“…20 Tau is cleaved at Aspartate 421 (D 421 ) by caspases into two peptides. Although the short COOH-terminal Tau peptide has not been the subject of investigation, the NH2-terminal Tau fragment, called δTau, has been extensively analyzed.…”
Section: Introductionmentioning
confidence: 99%